Pengaruh Perbedaan Jenis Umpan pada Alat Tangkap Bubu Lipat terhadap Hasil Tangkapan Rajungan (Portunus Pelagicus) di Perairan Pantai Jumiang Kabupaten Pamekasan - Fahlevi, Muhammad Ridho Hafiz; Kusyairi, Achmad (Lembaga Yasin AlSys, 2026)
The blue swimming crab (Portunus pelagicus) is a high-value fishery commodity that is extensively exploited by fishers in the coastal waters of Jumiang Beach, Pamekasan Regency, using collapsible traps (bubu lipat) as the main fishing gear, which belong to the trap category. This study aimed to analyze the effect of different bait types used in bubu lipat traps on blue swimming crab catches. An experimental method was employed with three bait treatments: A: pepetek fish (Leiognathus sp.), B: chicken intestines, and C: snails. Catch data were analyzed using an F-test. The results showed that pepetek fish bait yielded 25 crabs with a total weight of 2.115 kg, chicken intestine bait yielded 26 crabs with a total weight of 2.054 kg, and snail bait yielded 28 crabs with a total weight of 1.986 kg. Based on the F-test for catch numbers (individuals), a significance value of 0.147 (> 0.05) was obtained, while for catch weight (kg), the significance value was 0.072 (> 0.05). Thus, it can be concluded that differences in bait type in the operation of bubu lipat traps did not have a significant effect on the number of blue swimming crab catches, either in terms of individuals or weight. These findings indicate that the choice among the three bait types used does not constitute a key differentiating factor in optimizing blue swimming crab (Portunus pelagicus) catches with bubu lipat traps in the coastal waters of Jumiang Beach.